(untitled) (Global Journal of Science Frontier Research, 2021)
The issue of land-use conflict between farmers and pastoralists of recent had become an alarming situation which requires urgent attention due to its nature and effects in term of socio-economic imbalance, poor welfare, political indifference, cultural and ethnic belief. This study analyses Land-use Conflict between Farmers and Pastoralist in Gwagwalada Area Council, Abuja, Nigeria. Data were source using a structured questionnaire. 400 questionnaire were administered to 10 selected wards in Gwagwalada Area Council. Purposive and multi-stage techniques were used for this study. 322 questionnaires were administered to the farmers while 78 were for the pastoralist. Descriptive statistics such as; mean, standard deviation, and Wilcox on Sum Rank Test (WSRT) analysis were employed in the analysis. The study reveals that blockage and reduction of the size of the stock route and access to water points are the major causes of conflict between the farmers and pastoralists. On the effect of the of land-use conflict; farmers identify destruction of crops (mean=3.6), follow by mean=2.8 on the displacement of farmers/Fulanis, and mean= 2.4 on Loss of house, while pastoralist’s Major effects of the conflict were; mean=5.1 on the loss of lives/cattle, follow by mean=4.8 on Loss of houses and properties amongst others.